Pengaruh Lingkungan Kerja, Motivasi dan Kompensasi terhadap Kinerja Karyawan pada PT Putra Jaya Nanas - Adelya Putri Ari Wibowo; Muhammad Alhada Fuadilah Habib (Universitas 45 Surabaya, 2024)
Good employee performance is certainly due to several factors that encourage this. Some factors that affect employee performance such as work environment, motivation, and compensation. The purpose of this study was to (1) test the significant effect of work environment, motivation, and compensation on employee performance at PT Putra Jaya Nanas, (2) test the significant effect of work environment on employee performance at PT Putra Jaya Nanas, (3) test the significant effect of motivation on employee performance at PT Putra Jaya Nanas, (4) test the significant effect of compensation on employee performance at PT Putra Jaya Nanas. This research uses a quantitative approach with an associative research type. The sampling technique used is saturated sample. The type of data used is primary data obtained from distributing questionnaires to respondents, namely employees. questionnaire data obtained is processed using SPSS Version 16 by conducting validity tests, reliability tests, multicollinearity tests, multiple linear regression tests, coefficient of determination (R2) tests, F tests, T tests, normality tests, heteroscedasticity tests, and autocorrelation tests. The results showed that, (1) Work Environment, Motivation, and Compensation simultaneously affect Employee Performance at PT Putra Jaya Nanas, (2) Work Environment has a positive and significant effect on Employee Performance at PT Putra Jaya Nanas, (3) Motivation has a positive and significant effect on Employee Performance at PT Putra Jaya Nanas, (4) Compensation has a negative and significant effect on Employee Performance at PT Putra Jaya Nanas.